Sekularisme dan penolakan konsep khilafah - Zainuddin Losi; Umi Umairah Suhardi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Secularism is not originally part of the tradition of Islamic political thought. However, since the collapse of the Caliphate in 1924, governance systems in many Muslim-majority countries have been largely influenced by Western models based on secular principles, such as republics and monarchies. This shift has significantly affected how Muslims perceive political authority in Islam. The secular paradigm, initially employed by Orientalists to criticize and reject the Caliphate, was gradually adopted by some Muslim intellectuals. As a result, secularism became a standard framework for evaluating the relevance of the Caliphate, leading to the assumption that Islamic teachings must be adjusted when they do not align with secular values. In fact, secularism originates from Western intellectual traditions that fundamentally differ from Islamic paradigms. Furthermore, negative perceptions of the Caliphate are often shaped by positivist approaches, which rely on empirical reality as the primary of truth. This perspective has further reinforced contemporary rejection of the Caliphate in modern discourse.